Comparative efficacy and safety of multimodality treatment for advanced hepatocellular carcinoma with portal vein tumor thrombus: patient-level network meta-analysis - Leung, John Hang; Wang, Shyh-Yau; Leung, Henry W. C.; Chan, Agnes L. F. (Frontiers in Oncology, 2024)
Background Portal vein tumor thrombus (PVTT) is a common complication and an obstacle to treatment, with a high recurrence rate and poor prognosis. There is still no global consensus or standard guidelines on the management of hepatocellular carcinoma (HCC) with PVTT. Increasing evidence suggests that more aggressive treatment modalities, including transarterial chemoembolization, radiotherapy, targeted therapy, and various combination therapies, may improve the prognosis and prolong the survival of advanced hepatocellular carcinoma (aHCC) patients with PVTT. We aim to comprehensively review and compare the efficacy and safety of these advanced options for aHCC with PVTT. Methods A comprehensive literature search was conducted on PubMed and EMBASE for phase II or III randomized controlled trials (RCTs) investigating multimodality treatments for aHCC with PVTT. Kaplan–Meier curves for overall survival (OS) and progression-free survival were constructed to retrieve individual patient-level data to strengthen the comparison of the benefits of all multimodality treatments of interest. Each study was pooled in a fixed-effects network meta-analysis (NMA). We also conducted subgroup analyses using risk ratios extracted from each study, including viral etiology, Barcelona Clinic Liver Cancer (BCLC) staging, alpha-fetoprotein (AFP) levels, macrovascular invasion or portal vein tumor thrombosis, and extrahepatic spread. Multimodality treatments were ranked using SUCRA scores. Results We identified 15 randomized controlled trials with 16 multimodality regimens that met the inclusion criteria. Among them, 5,236 patients with OS results and 5,160 patients with PFS results were included in the analysis. The hepatic arterial infusion chemotherapy of fluorouracil, leucovorin, and oxaliplatin (HAIC-FO) showed OS and PFS benefits over all the other therapies. In terms of OS, HAIC-FO, nivolumab, and TACE+Len were superior to sorafenib, lenvatinib, and donatinib monotherapies, as well as HAIC-FO+Sor. In terms of PFS, TACE+Len showed better benefits than lenvatinib, donatinib, and tremelimumab+durvalumab. A low heterogeneity (I2 < 50%) and consistency were observed. The SUCRA score for OS ranked HAIC-FO+sorafenib as the best treatment option among all multimodality treatments in hepatitis B, MVI, or PVTT with EHS and AFP 400 μg/L subgroups. Conclusion HAIC-FO and HAIC-FO+sorafenib are statistically better options for unresectable hepatocellular carcinoma with PVTT among the multimodality treatments, and their effective and safe implementation may provide the best outcomes for HCC-PVTT patients.